Multiple Perspectives on the Quality of Programs for Young Children - Katz, Lilian G. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
This paper comments on issues of quality in early child care and education from an international perspective, asserting that questions about how to determine quality are as complex for early childhood programs as for all other professional services. The paper's introduction discusses the world wide trend of expansion in the amount of out-of-home care offered, the variations in training and government supervision, and the common problems of defining the objectives of early childhood provisions and of providing quality and affordability. The paper then lists five perspectives on assessing quality and states that criteria representing all of these perspectives merit consideration in determining the quality of provisions for the care and education of young children. Each perspective is discussed in detail: (1) the top-down perspective, which typically assesses selected characteristics of the program, setting, equipment, and other features, as seen from above by adults in charge of the program or by those responsible for licensing it; (2) the bottom-up perspective, which attempts to determine how the program is actually experienced by the participating children; (3) the outside-inside perspective, which assesses how the program is experienced by the families it serves; (4) the inside perspective, which considers how the program is experienced by its staff; and (5) the outside perspective, which takes into account how the community and larger society are served by the program. The paper then discusses implications suggested by this formulation of quality assessment, including discrepancies between perspectives, issues of accountability, and the use of high- versus low-inference variables (for example, having to infer deep feelings of participants versus measuring the staff-to-child ratio). The paper concludes that answers to the criteria proposed for each perspective can be used as a basis for decisions about the kinds of modifications to make to the program, but that efforts must continue in developing, adopting, and applying an accepted set of professional standards of practice for which practitioners can fairly be held accountable. Contains 22 references. (EV)
ERIC Note: Keynote address at the International Conference of the World Organization for Early Childhood Education (4th, Hong Kong, March 20-21, 1999).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Context; Early Childhood Education; Educational Assessment; Educational Environment; Educational Quality; Evaluation Criteria; Perspective Taking; Program Evaluation; Program Improvement; Standards; Day Care Quality; Quality Indicators; Information Analyses; Speeches/Meeting Papers; Multilingual/Bilingual Materials